SUPORTE SOCIAL E QUALIDADE DE VIDA EM IDOSOS PARTICIPANTES DE UM PROGRAMA DE EDUCAÇÃO PERMANENTE - Ferreira, Sueli (2012)
This study was intended to identify and describe a possible relationship between social support and quality of life in elderly participants in a continuing education program, which is promoted by a public agency in partnership with a University, located in one of the cities of the ABC region in São Paulo. The sample consisted of 106 individuals of both genders ranging in age from 60 years on, who effectively participate in the program. For data collection, the sample was divided into two subgroups, where the first group consisted of 54 seniors who have been attending the program for less than one year, and the other group consisted of 52 seniors who have been attending the program for more than one year, with the objective of identifying a possible existence of different perceptions between the groups, of the variables analyzed, depending on the time of participation in the program, which was not confirmed, as the results pointed to a homogeneity between the groups, both in the socioeconomic aspects and the perceptions of social support and quality of life, regardless of the time of participation in the program. This study used the exploratory descriptive method of comparative and quantitative character. The Scale of Perceived Social Support (SPSS) was used for data collection, which assesses the perception of social support in their emotional and practical dimensions; the instrument for evaluating the quality of life: WHOQOL Old & Bref; and a questionnaire with socioeconomic data that helped to characterize the profile of the sample and the statistical analysis of results. The results indicated that the sample studied is characterized by having a distinctive socioeconomic profile, with regard to higher education and monthly income, compared to the national average that presents a more vulnerable profile of the elderly Brazilian, with low education and income. The results of the evaluations of social support and quality of life perceptions have demonstrated that these seniors feel satisfied with their moment in life; and perceive the emotional support, feeling themselves as the object of affection in their social network. Regarding the perception of practical support, the results showed that the elderlies have a relative perception, pointing to uncertainties and doubts about receiving such support from their social network. Given this result, the perception of doubt and uncertainty in receiving practical support, and the distinctive socioeconomic characteristic of the sample, we can assume that these elderly people have these perceptions, by feeling themselves or by being in fact providers and not dependent on their social network. An inverse and negative correlation between the levels of social support and the quality of life facets was evident, suggesting that the social support construct may be perceived by the elderlies in the sample as a diminishing factor of biopsychosocial functionality or of behavioral competence.